Construction and flow cytometric screening of targeted enzyme libraries - Varadarajan, Navin; Cantor, Jason R; Georgiou, George; Iverson, Brent L (Nature protocols, 2009)
Herein, we describe a methodology for the construction of targeted libraries intended to modify the substrate specificity of proteases expressed on the cell surface of Escherichia coli . The native outer membrane protease, OmpT, is used as a model system. The protocol relies on gene assembly using oligonucleotides and is easily adaptable to any enzyme in which information is available on the putative active site residues. Increasingly complex libraries can be generated in a systematic manner and screened using flow cytometry (fluorescence-activated cell sorting, FACS) for variants displaying altered function. Furthermore, if the substrate-binding pockets have not been elucidated, a protocol for partial multi-site saturation library construction is presented that allows for sampling a large number of residues, while maintaining an appropriate level of protein function. The entire procedure, from start to finish, should take approximately 2–3 weeks.